A novel single-stranded RNA virus isolated from a phytopathogenic filamentous fungus, Rosellinia necatrix, with similarity to hypo-like viruses - Zhang, Rui; Liu, Shengxue; Chiba, Sotaro; Kondo, Hideki; Kanematsu, Satoko; Suzuki, Nobuhiro (Frontiers in Microbiology, 2014)
Here we report a biological and molecular characterization of a novel positive-sense RNA virus isolated from a field isolate (NW10) of a filamentous phytopathogenic fungus, the white root rot fungus that is designated as Rosellinia necatrix fusarivirus 1 (RnFV1). A recently developed technology using zinc ions allowed us to transfer RnFV1 to two mycelially incompatible Rosellinia necatrix strains. A biological comparison of the virus-free and -recipient isogenic fungal strains suggested that RnFV1 infects latently and thus has no potential as a virocontrol agent. The virus has an undivided positive-sense RNA genome of 6286 nucleotides excluding a poly (A) tail. The genome possesses two non-overlapping open reading frames (ORFs): a large ORF1 that encodes polypeptides with RNA replication functions and a smaller ORF2 that encodes polypeptides of unknown function. A lack of coat protein genes was suggested by the failure of virus particles from infected mycelia. No evidence was obtained by Northern analysis or classical 5′-RACE for the presence of subgenomic RNA for the downstream ORF. Sequence similarities were found in amino-acid sequence between RnFV1 putative proteins and counterparts of a previously reported mycovirus, Fusarium graminearum virus 1 (FgV1). Interestingly, several related sequences were detected by BLAST searches of independent transcriptome assembly databases one of which probably represents an entire virus genome. Phylogenetic analysis based on the conserved RNA-dependent RNA polymerase showed that RnFV1, FgV1, and these similar sequences are grouped in a cluster distinct from distantly related hypoviruses. It is proposed that a new taxonomic family termed Fusariviridae be created to include RnFV1 and FgV1.